Implementasi Energi Baru dan Terbarukan Pada Kendaraan Listrik Dapat Berkontribusi Dalam Mendukung Kebijakan Transisi Energi Nasional di Indonesia - Tajali Yudhanto; I Gusti Ayu Ketut Rachmi Handayani; Fatma Ulfatun Najicha (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
The acceleration of the Battery Electric Vehicle (BEV) program constitutes an integral part of Indonesia’s national strategy to reduce greenhouse gas emissions and to support the transition toward cleaner and more sustainable energy. Although regulated under Presidential Regulation No. 55 of 2019 and its implementing regulations, the existing legal framework governing BEVs remains sectoral in nature and has not been able to adequately address the complex environmental and economic challenges that arise, particularly those related to nickel mining as the primary raw material for batteries, the management of end-of-life battery waste, and the dependence of charging infrastructure on fossil-based energy sources. This article aims to analyze the urgency of establishing a specific law on BEVs as a comprehensive and integrated regulatory framework. This study employs normative legal research using statutory and conceptual approaches. The findings indicate that the absence of a specific law on BEVs may lead to legal uncertainty, increased environmental risks, and suboptimal achievement of national energy transition targets. Therefore, the establishment of a specific law governing BEVs is an urgent necessity to ensure legal certainty, environmental protection, and the sustainability of green economic development in Indonesia.